Incentivizing community health workers for scaling up mental health care in rural communities in India: A critical look at principles that work - Daniel, Mercian; Maulik, Pallab K. (Frontiers in Health Services, 2023)
Given the low availability of trained mental health professionals, there is evidence on task sharing where basic mental healthcare can be provided by trained community health workers (CHWs). A potential way to reduce the mental health care gap in rural and urban areas in India is to utilize the services of community health workers known as Accredited Social Health Activists (ASHAs). There is a paucity of literature that have evaluated incentivizing NPHWs vis-à-vis maintaining a competent and motivated health workforce especially in the Asia and Pacific regions. The principles around what works and does not work in terms of a mix of incentive packages for CHWs, while providing for mental healthcare in rural areas have not been adequately evaluated. Moreover, performance-based incentives which are receiving increasing attention from health systems worldwide, though evidence on the effectiveness of these incentives in Pacific and Asian countries is limited. CHW programs that have shown to be effective rely on an interlinked incentive framework at the individual, community, and health system levels. Drawing learnings from the past eight years in implementing the SMART Mental Health Program in rural India, we critically examine some of the emerging principles in incentivizing ASHAs while scaling up mental healthcare in communities using a systems approach.